Saúde mental e futebol: os conhecimentos referentes à saúde mental de professores que atuam com o futebol - NASCIMENTO, Hugo Felipe Souza (2022)
The present work raises the question: what is the knowledge regarding the mental health of teachers who work with football education? and aims to analyze the knowledge related to mental health of teachers who work with soccer. the methodological path started with a brief bibliographical review, followed by an approach to field research. The subjects are five teachers who work in clubs and social projects, spaces located in Outeiro district of Belém/PA, Belém/Pa, Ananindeua/Pa, Castanhal/Pa. The results demonstrate that teachers approach the knowledge of psychology in their training in a simplified way, as well as try to insert the theoretical/practical knowledge of the subject in their pedagogical work and still see limitations regarding the practice of soccer and mental health. It is concluded at the end of our research that knowledge about psychology/mental health are elements integrated to the teacher's pedagogical work with soccer teaching, however, depending on its organization, it can influence the subject's subjectivity in a positive and/or negative way.